2016
DOI: 10.1103/physrevlett.117.077402
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Rotation of Polarized Light Emission from MonolayerWS2

Abstract: We control the linear polarization of emission from the coherently emitting K þ and K − valleys (valley coherence) in monolayer WS 2 with an out-of-plane magnetic field of up to 25 T. The magnetic-fieldinduced valley Zeeman splitting causes a rotation of the emission polarization with respect to the excitation by up to 35°and reduces the polarization degree by up to 16%. We explain both of these phenomena with a model based on two noninteracting coherent two-level systems. We deduce that the coherent light emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 44 publications
5
95
0
Order By: Relevance
“…A second cause for the decrease in the detected linear polarization can be dephasing induced during the PL lifetime [79]. Note that a smaller rotation angle of the PL with respect to the one observed in WSe 2 [50] and WS 2 [49] MLs (characterized by larger g factors) is indeed expected for a smaller exciton g factor measured in our sample.…”
Section: Rotation Of Valley Coherencementioning
confidence: 74%
See 2 more Smart Citations
“…A second cause for the decrease in the detected linear polarization can be dephasing induced during the PL lifetime [79]. Note that a smaller rotation angle of the PL with respect to the one observed in WSe 2 [50] and WS 2 [49] MLs (characterized by larger g factors) is indeed expected for a smaller exciton g factor measured in our sample.…”
Section: Rotation Of Valley Coherencementioning
confidence: 74%
“…Generation of valley coherence is achieved optically by linearly polarized excitation σ X , which results in strongly linearly polarized neutral exciton (X 0 ) emission [26]. Recent experiments have shown that this valley polarization can be rotated in ML WSe 2 and WS 2 [49][50][51], a first important step towards full control of valley states [87]. The MoS 2 ML is excited by a linearly polarized (σ X ) continuous wave He-Ne laser (1.96 eV) to generate valley coherence (i.e., optical alignment of excitons [80]).…”
Section: Rotation Of Valley Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Note added in proof : After submission of our manuscript, results demonstrating the rotation of the valley pseudospin by static magnetic fields were reported by other researchers 35,36 .…”
mentioning
confidence: 95%
“…Broken spatial inversion symmetry and strong spin-orbit interactions introduce valley-contrasting physical properties that enable manipulation of the valley pseudospin degree of freedom (DoF) [17]. Most notably, electrons and holes residing at the K and K ′ valleys possess opposite spin, orbital magnetic moment, and Berry curvature [8].…”
Section: Introductionmentioning
confidence: 99%